Derivation of the Hawking radiation for the four dimensional Schwarzschild black hole in anti de Sitter space - Quddus, Tahsin Nahian Bin (Brac University, 2022)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Physics.